Demon slayer = Kimetsu no yaiba. Volume 11, A close fight - Gotoge, Koyoharu, 1988-; Stan!, 1964- (Shonen Jump manga., 2020)
The battle against the powerful sibling demons Gyutaro and Daki is not going well. Although finally able to fight alongside Tanjiro against the monsters, Zenitsu, Inosuke and even the Hashira Tengen Uzui may all be overwhelmed. Battling even one of Lord Muzan's Twelve Kizuki is hard enough--can Tanjiro face two of them alone?